2015
DOI: 10.1586/14789450.2015.1069189
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput screening of cellular redox sensors using modern redox proteomics approaches

Abstract: Cancer cells are characterized by higher levels of intracellular reactive oxygen species (ROS) due to metabolic aberrations. ROS are widely accepted as second messengers triggering pivotal signaling pathways involved in the process of cell metabolism, cell cycle, apoptosis, and autophagy. However, the underlying cellular mechanisms remain largely unknown. Recently, accumulating evidence has demonstrated that ROS initiate redox signaling through direct oxidative modification of the cysteines of key redox-sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 121 publications
0
7
0
Order By: Relevance
“…Redox sensor proteins are involved in detecting the dynamic balance between oxidants and antioxidants in the cell and driving the intracellular feedback mechanisms to increase the synthesis of important endogenous antioxidant systems or to regulate intracellular ROS signalling (Brigelius‐Flohe & Flohe, ). High‐throughput screening of cellular redox sensors using modern redox proteomics revealed that redox‐related transcription factors NRF2 and HIF are promising targets for modulation, especially on the antioxidant side of the balance (Jiang, Wang, Nice, Zhang, & Huang, ; Figure b).…”
Section: Molecular Targets For Tissue Engineersmentioning
confidence: 99%
“…Redox sensor proteins are involved in detecting the dynamic balance between oxidants and antioxidants in the cell and driving the intracellular feedback mechanisms to increase the synthesis of important endogenous antioxidant systems or to regulate intracellular ROS signalling (Brigelius‐Flohe & Flohe, ). High‐throughput screening of cellular redox sensors using modern redox proteomics revealed that redox‐related transcription factors NRF2 and HIF are promising targets for modulation, especially on the antioxidant side of the balance (Jiang, Wang, Nice, Zhang, & Huang, ; Figure b).…”
Section: Molecular Targets For Tissue Engineersmentioning
confidence: 99%
“…Several patterns of oxidative modifications have been reported, including sulfenylation (-SOH), sulfinylation (-SO 2 H), sulfonylation (-SO 3 H), S-glutathionylation (PrS-SG) and disulfide bonds (intramolecular, intermolecular and mixed types). 22 Through these redox modifications, ROS can alter the biological functions of redox-sensitive proteins involved in ECM remodeling (for example, integrin, Hu antigen R), cytoskeleton remodeling (for example, actin, cofilin), cell–cell junctions (for example, NF-κB, HIF-1α, TGF-β) and cell mobility (for example, Src, FAK, PTEN), thereby regulating EMT initiation and cancer cell progression. 9 …”
Section: Introductionmentioning
confidence: 99%
“…Establishing a 3D niche at the specific ratio of 50:50 INS1E:alphaTC1 cells was essential for protecting both cell types against oxidative stress. As a future outlook, it would be interesting to validate this finding in the context of beta cell replacement strategies, where the cells are known to experience high levels of oxidative stress [31,32,[43][44][45]. Engineered islets could be transplanted in the ratio of 50:50 beta:alpha cells to protect them against the oxidative stress they experience during transplantation and from biomaterials used for encapsulation [46].…”
Section: Discussionmentioning
confidence: 96%